2018
DOI: 10.1007/s11684-018-0646-8
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular and extracellular TGF-β signaling in cancer: some recent topics

Abstract: Transforming growth factor (TGF)-β regulates a wide variety of cellular responses, including cell growth arrest, apoptosis, cell differentiation, motility, invasion, extracellular matrix production, tissue fibrosis, angiogenesis, and immune function. Although tumor-suppressive roles of TGF-β have been extensively studied and well-characterized in many cancers, especially at early stages, accumulating evidence has revealed the critical roles of TGF-β as a pro-tumorigenic factor in various types of cancer. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
119
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 119 publications
(121 citation statements)
references
References 231 publications
(275 reference statements)
1
119
0
1
Order By: Relevance
“…Many tumor types are characterized by a high concentration of transforming growth factor-bs (TGFbs), which are produced by cancer cells and infiltrating inflammatory cells. Previous studies have shown that TGF-b promotes epithelial-to-mesenchymal transition (EMT) of normal and transformed epithelial cells, as well as EndMT of endothelial cells (Miyazono et al, 2018;Yoshimatsu and Watabe, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Many tumor types are characterized by a high concentration of transforming growth factor-bs (TGFbs), which are produced by cancer cells and infiltrating inflammatory cells. Previous studies have shown that TGF-b promotes epithelial-to-mesenchymal transition (EMT) of normal and transformed epithelial cells, as well as EndMT of endothelial cells (Miyazono et al, 2018;Yoshimatsu and Watabe, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It suppresses tumour progression by promoting cell cycle arrest and apoptosis in early-stage of pancreatic carcinogenesis. On the other hand, it functions as a tumour promoter by activating the Smad4-independent signalling pathway, promoting cell motility, invasion, EMT, and metastasis and decreasing anti-tumour immune responses in advanced stages 30 . Thus, inhibition of TGF-β signalling in the late stages of cancer progression could be an effective strategy for treating pancreatic cancer.…”
Section: Ectopic Expression Of Ccdc80 In Pancreatic Cancer Cells Decrmentioning
confidence: 99%
“…Across a variety of cancers, TGFβ plays crucial roles in EMT, tumor metastasis, angiogenesis, and treatment resistance [19]. Due to the celltype specific role of TGFβ as opposed to a cancer-specific role, understanding the pathways and modulatory factors of TGFβ are crucial to developing a broad-spectrum cancer treatment [20].…”
Section: Tgfβ Preclinical Developmentmentioning
confidence: 99%